Tick vaccines and the control of tick-borne pathogens - Merino, Octavio; Alberdi, Pilar; Pérez de la Lastra, José Manuel; de la Fuente, José (Frontiers in Cellular and Infection Microbiology, 2013)
Ticks are obligate hematophagous ectoparasites that transmit a wide variety of pathogens to humans and animals. The incidence of tick-borne diseases has increased worldwide in both humans and domestic animals over the past years resulting in greater interest in the study of tick–host–pathogen interactions. Advances in vector and pathogen genomics and proteomics have moved forward our knowledge of the vector-pathogen interactions that take place during the colonization and transmission of arthropod-borne microbes. Tick-borne pathogens adapt from the vector to the mammalian host by differential gene expression thus modulating host processes. In recent years, studies have shown that targeting tick proteins by vaccination can not only reduce tick feeding and reproduction, but also the infection and transmission of pathogens from the tick to the vertebrate host. In this article, we review the tick-protective antigens that have been identified for the formulation of tick vaccines and the effect of these vaccines on the control of tick-borne pathogens.